Streamlined Human Cell-Based Recombinase-Mediated Cassette Exchange Platform Enables Multigene Expression for the Production of Therapeutic Proteins - Shin, Seunghyeon; Kim, Su Hyun; Lee, Jae Seong; Lee, Gyun Min (ACS Synthetic Biology, 2021)
A platform, based on targeted integration of transgenes using recombinase-mediated cassette exchange (RMCE) coupled with CRISPR/Cas9, is increasingly being used for the development of mammalian cell lines that produce therapeutic proteins, because of reduced clonal variation and predictable transgene expression. However, low efficiency of the RMCE process has hampered its application in multicopy or multisite integration of transgenes. To improve RMCE efficiency, nuclear transport of RMCE components such as site-specific recombinase and donor plasmid was accelerated by incorporation of nuclear localization signal and DNA nuclear-targeting sequence, respectively. Consequently, the efficiency of RMCE in dual-landing pad human embryonic kidney 293 (HEK293) cell lines harboring identical or orthogonal pairs of recombination sites at two well-known human safe harbors (AAVS1 and ROSA26 loci), increased 6.7- and 8.1-fold, respectively. This platform with enhanced RMCE efficiency enabled simultaneous integration of transgenes at the two sites using a single transfection without performing selection and enrichment processes. The use of a homotypic dual-landing pad HEK293 cell line capable of incorporating the same transgenes at two sites resulted in a 2-fold increase in the transgene expression level compared to a single-landing pad HEK293 cell line. In addition, the use of a heterotypic dual-landing pad HEK293 cell line, which can incorporate transgenes for a recombinant protein at one site and an effector transgene for cell engineering at another site, increased recombinant protein production. Overall, a streamlined RMCE platform can be a versatile tool for mammalian cell line development by facilitating multigene expression at genomic safe harbors.
Keywords: Biological Transport; Cell Nucleus; DNA Nucleotidyltransferases; Gene Expression; HEK293 Cells; Humans; Recombinant Proteins; Transfection; Transgenes; human cell engineering; multigene expression; nuclear transport; recombinase-mediated cassette exchange; targeted integration; therapeutic proteins